Using nudging information to manage congestion and emissions in a road and metro network - Zhiyuan Liang; Vincent A. C. van den Berg; Erik T. Verhoef; Yacan Wang (Tinbergen Institute, 2024)
This study studies nudging information as a strategy that can complement or substitute externality pricing, by influencing commuter behavior through awareness of the health and environmental impacts of their choices. We develop a bi-modal model with road and metro commuters, with bottleneck congestion on the road and dynamic crowding congestion in the metro. The model further incorporates health costs and environmental externalities, particularly for road commuters. When commuters are homogeneous, our findings indicate that nudging information generates positive welfare effects except in scenarios with extremely high crowding effects in the metro system. Moreover, nudging information can consistently complement flat road tolls by integrating information and toll schemes to enhance the system's social welfare impact. By adding heterogeneity in environmental preferences, car types, and income, the study further highlights that the effectiveness of such strategies depends on the varied behavioral responses from diverse individuals. Even when the crowding effect is relatively small with heterogeneity, nudging information may result in negative welfare effects by causing welfare-reducing swaps in road commuters' departure patterns; in such cases, it fails to complement flat tolls effectively
Keywords: 330; Congestion; Emissions; Nudging information; Bi-modal; Heterogeneity